Effect of Three Common Desensitizers in Reduction of the Dentin Hypersensitivity after Periodontal Surgery - Salahi S; Ghanbari M; Moosaali F (Shiraz University of Medical Sciences, 2016)
Statement of Problem: Dentin hypersensitivity is one of the most common complaints of patients after periodontal treatments which occur after tissue shrinkage. Objectives: The aim of this study was to determine and compare the effectiveness of sensikin gel (10% potassium nitrate and 0.22% sodium fluoride) with sodium fluoride gel (2.7%) and fluoride varnish (5%) in reducing the dentin hypersensitivity after periodontal surgery. Materials and Methods: Twenty-two patients who, after full mouth periodontal surgery, had a complaint of dentin hypersensitivity (DH) in at least three quadrants were selected. Then a specific treatment was randomly selected for each quadrant which was applied once a day for one week and then stopped. A visual analog scale (VAS) was used to assess the subjects' responses to air blast and periodontal probe stimuli at baseline at one week, and one, three and 6 months after treatment. To analyze the data, repeated measures ANOVA test, Tukey test and variance analysis test were used. Results: At all given intervals, almost both sodium fluoride and sensikin gel significantly reduced the dental sensitivity caused by stimulants. There were no significant differences between sensikin gel and other two desensitizers in reducing the dentin hypersensitivity after 1 week, 1 month, 3 months, and 6 months with respect to air blast stimuli. Sensikin gel was more efficient than Fluoride varnish in reducing the sensitivity caused by periodontal probe after 1 month. Conclusions: Sensikin gel, sodium fluoride gel and fluoride varnish can all be prescribed to reduce dental sensitivity in patients who have undergone periodontal treatments. In the case of severe sensitivity to mechanical stimulations, a treatment with a long-run effectiveness such as sensikin and/or sodium fluoride gel is preferred.